Effect of dietary atung seed flour (Parinarium glaberrimum) on small intestine characteristics of broiler chickens - INSUN SANGADJI; SYLVIA C. H. HEHANUSSA; RONY MARSYAL KUNDA (Smujo International, 2024)
Abstract. Sangadji I, Hehanussa SCH, Kunda RM. 2024. Effect of dietary atung seed flour (Parinarium glaberrimum) on small intestine characteristics of broiler chickens. Nusantara Bioscience 16: 277-283. This study was conducted to investigate the effect of feeding atung (Parinarium glaberrimum Hassk.) seed meal on intestinal microflora, pH, and micro-morphology in broiler chickens. A total of 168-day-old male New Lohmann broiler chickens were randomly assigned to six treatment groups with four replicates and seven birds in each replicate pen. The dietary treatments consisted of feeding the same corn-soybean meal basal diet with atung seed meal inclusions at levels of 0, 0.5, 1.0, 2.0, and 4.0%, respectively. Basal diet inclusion with 50 ppm of tetracycline was also used as a positive control treatment. The data was statistically analyzed using ANOVA in a completely randomized design, a robust methodology, and continued subsequently with Duncan's test for data with significant differences. Results showed that the number of lactic acid bacteria, duodenal and ileal villus height, villus width, and villus height to crypt depth ratio was increased (p<0.05) with the inclusion of 0.5-1.0% atung seed meal. Coliform numbers and intestinal pH were decreased (p<0.01) with 1.0% atung seed meal inclusion. With respect to the results of some response variables of intestinal pH and micro-morphology, additions of atung seed meal showed better results than the addition of 50 ppm tetracycline. It can be concluded that atung seed can be recommended as a green feed additive for replacing antibiotic growth promoters in the poultry diet based on the ability to improve gut microflora and micro-morphology.